The Hidden Effects of Child Maltreatment in a War Region: Correlates of Psychopathology in Two Generations Living in Northern Uganda. Issue 1 (29th January 2014) - Olema, David Kani; Catani, Claudia; Ertl, Verena; Saile, Regina; Neuner, Frank
Abstract: Adverse life experiences are a major risk factor for psychopathology. Studies from industrialized countries have consistently shown the detrimental effects of child maltreatment on the mental health of the victims. Research in war‐affected populations, however, has mostly been restricted to the psychological damage caused by the war. Both war trauma and child maltreatment have rarely been studied simultaneously. In a comparative study of 2 generations living in severely war‐affected regions in Northern Uganda, we determined the relationship between both trauma types and posttraumatic stress disorder (PTSD), anxiety, depression, and suicide ideation. A total of 100 adolescents, 50 with and 50 without a history of abduction by the rebel army with both their parents (100 mothers and 100 fathers) living in camps in northern Uganda were interviewed. The study showed that both generations were severely affected by war and child maltreatment. Both trauma types were independently correlated with psychological disorders in the adolescent group. Only child maltreatment, however, not war violence, accounted for PTSD symptoms in the parent group (β = .253, p = .002). We conclude that, even in the context of severe war, the impact of child maltreatment on psychological disorders surpasses the damage of war trauma.